PENGARUH KUALITAS PELAYANAN DAN WORD OF MOUTH ( WOM ) TERHADAP KEPUTUSAN PEMBELIAN - Herawati, Heny (Kinerja, 2020)
This study aims to determine the influence of Service Quality and Word of Mouth (WOM) on Purchasing Decisions at PT. Hijrah Insan Karima because at this time there have been many threats and competitors in the world of selling concrete and baja ringan iron. The subject in this study was the Histeel company that had been established since 2008. The total population studied in this study was 465,000 respondents. The sampling technique uses slovin formula and obtained a sample of 100 respondents, namely consumers PT. Hijrah Insan Karima. The statistical methods used in this study are the Classical Assumption test, Regression Analysis, Correlation Analysis, and Hypothesis Test. The analytical tool used in this study is SPSS version 21. The results of this study indicate that Service Quality and Word of Mouth (WOM) simultaneously have a significant effect on purchasing decisions. Tested with multiple correlations, there is a simultaneous contribution value of R = 0.592 or 59.2% influential and 40.8% influenced by other variables and the results of the t test sig X1 value of 0.006 <0.05 and X2 of 0.000 <0.05 means Service Quality and Word of Mouth (WOM) variables influence Purchasing Decisions.